The Effect of Age on Mortality in Patients With COVID-19: A Meta-Analysis With 611,583 Subjects - Bonanad, Clara; García-Blas, Sergio; Tarazona-Santabalbina, Francisco; Sanchis, Juan; Bertomeu-González, Vicente; Fácila, Lorenzo; Ariza, Albert; Núñez, Julio; Cordero, Alberto (Journal of the American Medical Directors Association, 2020)
Initial data on COVID-19 infection has pointed out a special vulnerability of older adults. We performed a meta-analysis with available national reports on May 7, 2020 from China, Italy, Spain, United Kingdom, and New York State. Analyses were performed by a random effects model, and sensitivity analyses were performed for the identification of potential sources of heterogeneity. COVID-19-positive patients reported in literature and national reports. All-cause mortality by age. A total of 611,1583 subjects were analyzed and 141,745 (23.2%) were aged ≥80 years. The percentage of octogenarians was different in the 5 registries, the lowest being in China (3.2%) and the highest in the United Kingdom and New York State. The overall mortality rate was 12.10% and it varied widely between countries, the lowest being in China (3.1%) and the highest in the United Kingdom (20.8%) and New York State (20.99%). Mortality was <1.1% in patients aged <50 years and it increased exponentially after that age in the 5 national registries. As expected, the highest mortality rate was observed in patients aged ≥80 years. All age groups had significantly higher mortality compared with the immediately younger age group. The largest increase in mortality risk was observed in patients aged 60 to 69 years compared with those aged 50 to 59 years (odds ratio 3.13, 95% confidence interval 2.61-3.76). This meta-analysis with more than half million of COVID-19 patients from different countries highlights the determinant effect of age on mortality with the relevant thresholds on age >50 years and, especially, >60 years. Older adult patients should be prioritized in the implementation of preventive measures.